Photoregulation of Fructose and Glucose Respiration in the Intact Chloroplasts of Chlamydomonas reinhardtii F-60 and Spinach. - Singh, K. K. (1993)
The photoregulation of chloroplastic respiration was studied by monitoring in darkness and in light the release of 14CO2 from whole chloroplasts of Chlamydomonas reinhardtii F-60 and spinach (Spinacia oleracea L.) supplied externally with [14C] glucose and [14C]-fructose, respectively. CO2 release was inhibited more than 90% in both chloroplasts by a light intensity of 4 W m-2. Oxidants, oxaloacetate in Chlamydomonas, nitrite in spinach, and phenazine methosulfate in both chloroplasts, reversed the inhibition. The onset of the photoinhibitory effect on CO2 release was relatively rapid compared to the restoration of CO2 release following illumination. In both darkened chloroplasts, dithiothreitol inhibited release. Of the four enzymes (fructokinase, phosphoglucose isomerase, glucose-6-P dehydrogenase, and gluconate-6-P dehydrogenase) in the pathway catalyzing the release of CO2 from fructose, only glucose-6-P dehydrogenase was deactivated by light and by dithiothreitol.